3, 4‐diaminopyridine base effectively treats the weakness of Lambert‐Eaton myasthenia. Issue 4 (2nd February 2018) - Sanders, Donald B.; Juel, Vern C.; Harati, Yadollah; Smith, A. Gordon; Peltier, Amanda C.; Marburger, Tessa; Lou, Jau‐Shin; Pascuzzi, Robert M.; Richman, David P.; Xie, Tai; Demmel, Valentin; Jacobus, Laura R.; et al.
ABSTRACT: Introduction : 3, 4‐diaminopyridine has been used to treat Lambert‐Eaton myasthenia (LEM) for 30 years despite the lack of conclusive evidence of efficacy. Methods : We conducted a randomized double‐blind placebo‐controlled withdrawal study in patients with LEM who had been on stable regimens of 3, 4‐diaminopyridine base (3, 4‐DAP) for ≥ 3 months. The primary efficacy endpoint was >30% deterioration in triple timed up‐and‐go (3TUG) times during tapered drug withdrawal. The secondary endpoint was self‐assessment of LEM–related weakness (W‐SAS). Results : Thirty‐two participants were randomized to continuous 3, 4‐DAP or placebo groups. None of the 14 participants who received continuous 3, 4‐DAP had > 30% deterioration in 3TUG time versus 72% of the 18 who tapered to placebo ( P < 0.0001). W‐SAS similarly demonstrated an advantage for continuous treatment over placebo ( P < 0.0001). Requirement for rescue and adverse events were more common in the placebo group. Discussion : This trial provides significant evidence of efficacy of 3, 4‐DAP in the maintenance of strength in LEM. Muscle Nerve 57 : 561–568, 2018